Implementasi Inovasi Budidaya Stroberi di Agrowisata Banyuroto Kabupaten Magelang Melalui Education for Sustainable Development - Ganies Riza Aristya; Aries Bagus Sasongko; Lisna Hidayati; Agus Setiawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
The cultivation of strawberry needs of technological innovation to gain competitive advantage strawberry fruit quality and quantity. This is motivated because the decline in the production of strawberries in the area and quality of strawberry fruit is still low. Since 2012 until now, Laboratory of Genetics has identified and developed the character of phenotype and genotype of strawberry plants in Agro Banyuroto, Village Banyuroto Sawangan District of Magelang regency. Character genotypes studied through the identification of ploidy with cytogenetic approach and apply poliploidisasi technology that aims to double the number of sets of chromosomes in order to obtain a plant that has the character of superior phenotype compared with the control. The purpose of this activity was to awaken the capacity of communities that were able to develop and utilize natural resources to meet human needs while maintaining the environmental implementing action plans that lead to sustainable development in a sustainable manner. The method was executed in this activity was the cultivation of strawberries by exploiting natural resources Banyuroto village environment that was using bamboo, strawberry cultivation techniques with vertikultur systems. Moreover, the carrying capacity was also supported by the promotion of village tourism as central region Banyuroto strawberry cultivation of strawberries superior to tourists every week, promotion through Online system (in the network) by utilizing Information Technology and Computing and community empowerment with the diversification of food made from strawberries. The end result of this activity was obtained hallmarks of crops polyploidy were plant growth faster, the ability of the formation of stolons and nursery faster, leaf area and stem diameter was wider, the stem stout and roots were longer, the fruit produced was greater and a sweeter taste with more red fruit color. Innovation strawberry crop is expected to be followed by the cultivation of sustainable optimal as possible so that the results obtained are able to improve the welfare of farmers in Banyuroto strawberries.